Deletion of the Correia element in the mtr gene complex of Neisseria meningitidis - Enríquez, Rocío (2010)
The mtr gene complex in Neisseria meningitidis encodes an efflux pump that is responsible for export of antibacterial hydrophobic agents. The promoter region of the mtrCDE operon harbours an insertion sequence known as a Correia element, and a binding site for the integration host factor (IHF) is present at the centre of the Correia element. It has been suggested that the expression of the mtrCDE operon in meningococci is subject to transcriptional regulation by the IHF and post-transcriptional regulation by cleavage in the inverted repeat of the Correia element. The promoter region of the mtrCDE operon as well as the association of changes at that point with decreased susceptibility to antimicrobial drugs in 606 Neisseria meningitidis strains were analysed in this study. Two different deletions were present in the analysed region. The first one, found in seven strains, corresponded to absence of the Correia element. The second one, affecting the -10 region and first 100 bp of the mtrR gene and present in 57 isolates, was only found in ST-1624 isolates. None of the deletions were associated with decreased susceptibility to antimicrobial drugs. Although most of the meningococcal strains carry the Correia element at that position, its deletion is not an exception.